Weight functions for stress intensity factor and T-stress derived for an inclined edge crack in a finite width plate. (December 2022) - Leonetti, Davide; Vantadori, Sabrina
Abstract: The present paper discusses the formulation of weight functions for inclined edge cracks in finite width plates, typical of Rolling Contact Fatigue defects, to obtain the Stress Intensity Factor and the T-stress. Because the weight functions do not depend on the load and boundary conditions, their use is convenient to study cracks subjected to complex stress fields, e.g. fretting fatigue and rolling contact fatigue, since the stress field is calculated for the uncracked geometry. In this work, the weight functions are derived for both mode-I and mode-II of loading using the finite element method. Highlights: The weight functions for inclined edge cracks in finite width plates are formulated. Direct and indirect components of weight functions are derived. The weight functions are derived for both SIFs and T-stress.